The Analysis of Questioning Strategies Used by Lecturer in Reading Class - Dewi, Puspa (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This study analyses spoken discourse particularly the questioning strategies used by the lecturerduringteaching in Reading class in English Education Program. Questioning has long been used as a teaching tool by teachers and preceptors to assess studentsâ knowledge, promote comprehension, and stimulate critical thinking. This is a descriptive qualitative research using recorded class activity as the data. The unit of analysis is the questioning strategies used by the Reading lecturer. The result shows that during the recording, there are fifteen questions proposed by the lecturer. I consulted to the revised Bloomâs taxonomy in the field of cognitive domain to analyze the data. These results can be applied in the classroom and in experiential learning environments particularly in Reading class to enhance student engagement and promote critical thinking and higher-order learning.